Light-controlled bubble propulsion of amorphous TiO2/Au Janus micromotors. Issue 13 (26th January 2016) - Li, Yan; Mou, Fangzhi; Chen, Chuanrui; You, Ming; Yin, Yixia; Xu, Leilei; Guan, Jianguo
Abstract : The bubble-propelled amorphous TiO2 /Au Janus micromotors with the reversibly light-controlled motion state and speed have been demonstrated by utilizing the efficient photocatalytic H2 O2 decomposition over the in situ H2 O2 sensitized amorphous TiO2 . Abstract : In this work, a bubble-propelled photoactivated amorphous TiO2 /Au (Am-TiO2 /Au) Janus micromotor has been demonstrated by utilizing the efficient photocatalytic H2 O2 decomposition over the in situ H2 O2 sensitized Am-TiO2 under UV irradiation. The power conversion of the micromotor experiences a process from UV light power, to chemical power and finally to mechanical power. The quantum efficiency of O2 bubble evolution from photocatalytic decomposition of H2 O2 reaches 28%, and the power conversion efficiency reaches 1.28 × 10 −9, which enables the micromotor to generate a strong bubble thrust propelling itself forward with a maximum speed of 135 μm s −1 . The motion state and speed of the Am-TiO2 /Au micromotors can be reversibly, wirelessly and remotely controlled at will with an ultrafast response rate (less than 0.1 s) by regulating "on/off" switch and intensity of UV irradiation. Consequently, the as-developed Am-TiO2 /Au micromotors may promise potential challenging applications in such as "on-the-fly" adsorption and decomposition of pollutants in water.